(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Craftsmen’s traveling or itinerancy in the last century of the Roman Republic in the northeast of the Iberian Peninsula, is not justified, or not yet, on identifiable cases. However, it remains an interesting basis for reflection to better understand the work of artisans who have undeniable technical expertise, particularly in the field of Palaeohispanic scripts, since the distribution of inscriptions is geographically extensive and the local production is low. Taking into account the studies of practices in southern Iberia, Greece and Italy, I consider the role of the social context of handicrafts in the cultural transfers, then I deal with the mobility of artisans taking the case of monetary productions and finally I explore the possibility of stonecutter’s workshops in Hispania Citerior.